2014
DOI: 10.1117/12.2043067
|View full text |Cite
|
Sign up to set email alerts
|

Generalized least-squares CT reconstruction with detector blur and correlated noise models

Abstract: The success and improved dose utilization of statistical reconstruction methods arises, in part, from their ability to incorporate sophisticated models of the physics of the measurement process and noise. Despite the great promise of statistical methods, typical measurement models ignore blurring effects, and nearly all current approaches make the presumption of independent measurements – disregarding noise correlations and a potential avenue for improved image quality. In some imaging systems, such as flat-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…We evaluate the method by comparing reconstructions using the correlated noise model with results obtained using a model that assumes spatially independent noise. This work expands upon previous work where we have shown correlated noise models are advantageous when dealing with high readout noise and no source blur (Stayman et al 2014) and in more recent work in which we introduced a regularized deblurring step (Tilley II et al 2014). The latter work considered preliminary simulation studies with three different blur scenarios using a small phantom and demonstrated that systems dominated by detector blur with low readout noise do not benefit from the proposed model, but source blur dominated systems do.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We evaluate the method by comparing reconstructions using the correlated noise model with results obtained using a model that assumes spatially independent noise. This work expands upon previous work where we have shown correlated noise models are advantageous when dealing with high readout noise and no source blur (Stayman et al 2014) and in more recent work in which we introduced a regularized deblurring step (Tilley II et al 2014). The latter work considered preliminary simulation studies with three different blur scenarios using a small phantom and demonstrated that systems dominated by detector blur with low readout noise do not benefit from the proposed model, but source blur dominated systems do.…”
Section: Introductionsupporting
confidence: 54%
“…However, this assumption only holds for low readout noise. As shown in (Stayman et al 2014), a system dominated by detector blur will still benefit from a correlated noise model since deblurring will add correlations due to additive readout noise. The FDK and deblurred FDK resolution-variance points lie near the uncorrelated model's resolution-variance curve indicating similar performance.…”
Section: Simulation Studiesmentioning
confidence: 99%
“…Incorporation of such complexities into model-based statistical reconstruction is an area of ongoing and future work. 49 We consider a quadratic penalty, R(μ), of the form…”
Section: C the Spatially Varying Nps And Mtf For Iterative Statistmentioning
confidence: 99%
“…Therefore, Eq. (2) and (3) need to be re-written for consideration of correlations when dealing with these corrections and a generalized reconstruction model as in (Stayman et al 2014, Tilley et al 2014) may be required.…”
Section: Discussionmentioning
confidence: 99%